Isopoll Maps and an Analysis of the Distribution of the Modern Pollen Rain, Eastern and Central Northern Canada - Elliot-Fisk, D.; Andrews, J.; Short, S.; Mode, W. (Géographie physique et Quaternaire, 1982)
ABSTRACTAt 39 sites in eastern and central northern Canada, multiple samples of surface moss and lichens have been analyzed for their pollen content. Although pollen from 20 to 30 taxa were identified in the samples from each site, 8 pollen types (Alnus, Betula, Picea. Pinus, Salix, Gramineae, Cyperaceae and Ericaceae) usually comprise 90 to 100% of the pollen rain. We present isopoll maps of these taxa based on mean percentages of multiple samples from the 39 sites. The data are further analyzed by a number of statistical methods to determine whether there are specific pollen assemblages within this region and to what extent present day climatic parameters and floristic/vegetation zones correlate with pollen counts. Cluster analysis on raw data and on principal component scores yields six distinct pollen assemblages which are further examined by discriminant analysis. Pollen concentration maps for eastern Canada are also presented here and used as an aid in interpreting the percentage data.